754 Insomnia and Depression Symptoms in Primary Care Patients Referred for Mental Health Care. (3rd May 2021) - Vargas, Ivan; Muench, Alexandria; Seewald, Mark; Livesey, Cecilia; Press, Matthew; Oslin, David; Thase, Michael; Perlis, Michael
Abstract: Introduction: Past epidemiological research indicates that insomnia and depression are both highly prevalent and tend to co-occur in the general population. The present study further assesses this association by estimating: (1) the concurrence rates of insomnia and depression in outpatients referred by their primary care providers for mental health care; and (2) whether the association between depression and insomnia varies by insomnia subtype (initial, middle, and late). Methods: Data were collected from 3, 174 patients (mean age=42.7; 74% women; 50% Black) who were referred to the integrated care program for assessment of mental health symptoms (2018–2020). All patients completed an Insomnia Severity Index (ISI) and a Patient Health Questionnaire (PHQ-9) during their evaluations. Total scores for the ISI and PHQ-9 were computed. These scores were used to categorize patients into diagnostic groups for insomnia (no-insomnia [ISI < 8], subthreshold-insomnia [ISI 8–14], and clinically-significant-insomnia [ISI>14]) and depression (no-depression [PHQ-914]). Items 1–3 of the ISI were also used to assess the association between depression and subtypes of insomnia. Results: Rates of insomnia were as follows: 34.6% for subthreshold-insomnia, 35.5% for clinically-significant insomnia, and 28.9% for mild-depression and 26.9% for clinically-significant-depression. 92% of patients with clinically significant depression reported at least subthreshold levels of insomnia. While the majority of patients with clinical depression reported having insomnia, the proportion of patients that endorsed these symptoms were comparable across insomnia subtypes (percent by subtype: initial insomnia 63%; middle insomnia 61%; late insomnia 59%). Conclusion: According to these data, the proportion of outpatients referred for mental health evaluations that endorse treatable levels of insomnia is very high (approximately 70%). This naturally gives rise to at least two questions: how will such symptomatology be addressed (within primary or specialty care) and what affect might targeted treatment for insomnia have on health were it a focus of treatment in general? Support (if any): Vargas: K23HL141581; Perlis: K24AG055602